The Contribution of Assertive Technique Behavioral Counseling to Minimize the Juvenile Delinquency Behavior - Zadrian Ardi; Mey Sisin (Indonesian Institute for Counseling, Education and Therapy (IICET), 2018)
The purpose of this study was to determine the effectiveness of behavioral counseling using assertive technique to minimize the juvenile delinquency of students. This research is an experimental research design. The study population was the eighth grade students in South Solok West Sumatra consist of 82 students using Random Sampling. Data collection methods that used in this study were a questionnaire method. Data were analyzed by t-test with SPSS 20.0 for Windows. The results showed that there are significant differences between the groups which have deviant behavior who take behavioral counseling session with a group of students who do not follow the behavioral counseling session. It could be seen from a group of students who take behavioral counseling session (133.17) compare with a group of students who do not follow behavioral counseling session (85.32), and from the analysis of t with df = 82 and 1% significance level (t = 0.053, p <0.01). So the application of behavioral counseling Training assertive techniques to minimize misbehavior is effective to reduce the juvenile delinquency of students.